Building an Optimal Trade Portfolio for Indian Spices Exports by Mean Variance Optimization - Srinivasa Rao, D. (Indian Journal of Finance, 2013)
An attempt is made in this paper to build an optimized trade portfolio for Indian spices sector in the context of the projection that India is going to be the world’s processing hub of spices in the next ten years. The current Indian spices trade portfolio was constructed by estimating the weights of each of the fifteen spice items that constitute the trade portfolio and the trend of growth rates and instability indices for each of these items. The trend growth rates are considered as returns, and instability indices are considered as risks associated with each of the spice items in the trade portfolio. Using the mean variance optimization technique, a optimal portfolio that yields a 20% CAGR with minimum instability was obtained by utilizing the MATLAB program. The results indicate the need for reorganization of Indian spices trade portfolio in favour of value added items.